Chemically tailored carbon nanotubes as a new toolbox for biomedicine and beyond. (11th September 2019) - Barnes, Benjamin; Brozenay, Alexandra; Wang, YuHuang
Abstract : Like molecules of DNA, carbon nanotubes (CNTs) can display a variety of structures, but all conduct electrons and feature unique optical properties. In this perspective article, we highlight several recent works that bridge these two seemingly distant worlds. We illustrate the largely untapped potential of CNTs for biological research by exploring several developing biomedical applications utilizing nanotube semiconductors, including field effect transistor biosensors that couple high sensitivity with selectivity, and fluorophores for deep-tissue imaging whose excitation and emission wavelengths can be tuned throughout the near-IR II window simply by using defect chemistry.